Quantifying internal CO2 recycling for high-rate carbon capture in mixotrophic Scenedesmus acuminatus - Muhammad Muzammil Sultan; Muhammad Mubashar; Hira Ashfaq; Jing Li; Xuezhi Zhang (Bioresource Technology, 2026)

Correction to: Tracing Potentially Toxic Metals from Water to Soil, Maize, and Cow Milk: Food Chain Risks and Safety Concerns - Kafeel Ahmad; Mashal Maqsood; Zafar Iqbal Khan; Asma Ashfaq; Mutiya Zafar; Muhammad Mazhar Iqbal; Ijaz Rasool Noorka; Hafsa Memona; Farzana Siddique; Ilker Ugulu (Bulletin of Environmental Contamination and Toxicology, 2026)

Formulation and Evaluation of Losartan Potassium Microparticles Loaded Controlled-Release Tablets: An In-Vitro Perspective - Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Saima Mahmood; Farman Shah; Naveed Ullah; Fida Muhammad; Anam Adil; Sami ul Haq; Haroon Khan (Journal of Pharmaceutical Innovation, 2026)

Pollen micromorphological variations in selected species of genus Ipomoea (Convolvulaceae) and their taxonomic significance - Aleena Gul; Muhammad Zafar; Salman Majeed; Muhammad Rizwan Khan; Samah A. Alharbi; Sayyara Ibadullayeva; Shomaila Ashfaq; Khuzin Dinislam; Adnan Amin; Samira Khudaverdiyeva (Plant Biosystems, 2026)

Sustainable approaches to alleviate salinity stress in two fenugreek cultivars through moringa leaf extract and salicylic acid - Sumreen Anjum; Iqra Tabassam; Mubeen Sarwar; Tanveer Hussain; Shoaib ur Rehman; Sumaira Maqsood; M. Irfan Ashraf; Muhammad Ashfaq; Qurban Ali (Plant Biosystems, 2026)

Nickel and Cobalt Accumulation and Human Health Risk in Guava (Psidium guajava L.) Under Wastewater Irrigation: A Soil–Plant Transfer Assessment - Zafar Iqbal Khan; Kafeel Ahmad; Asma Ashfaq; Sana Anwar; Shahzad Akhtar; Ijaz Rasool Noorka; Muhammad Irfan Ashraf; Ilker Ugulu (Bulletin of Environmental Contamination and Toxicology, 2026)

Nanoparticles in potato disease management: Applications, mechanisms, and future perspectives for sustainable crop production - Aneeza Ishfaq; Ishrat Bano; Irfan Haidri; Muhammad Shahid; Muhammad Sohail Akram; Muhammad Khubeb Ashfaq; Sabir Hussain; Tanvir Shahzad; Faisal Mahmood (Physiological and Molecular Plant Pathology, 2026)

Geochemical Characterization of Saidgai and Katora Lakes for Irrigation, Drinking, and Health Risk Indices, Hindu Kush Region - Said Muhammad; Tufail Ahmad; Wajid Ali; Adnan Ali Khan; Cem Tokatli; Ashfaq Ahmad; Zafar Iqbal (Water, Air, & Soil Pollution, 2026)

The Evolution of Organoids: From Discovery to Cutting-Edge Applications - Javeria Umber; Uzair Ahmed; Tazeem Fatima; Muhammad Qasim; Usman Ali Ashfaq; Muhammad Shareef Masoud (Stem Cell Reviews and Reports, 2026)

Multilevel barriers to antimicrobial stewardship in tertiary care hospitals: A comparative systematic scoping review of high-income versus low-/middle-income countries evidence mapped by study design and healthcare professionals - Azfar Athar Ishaqui; Zikria Saleem; Tauqeer Hussain Mallhi; Sultan M. Alshahrani; Khalid Orayj; Salman Ashfaq Ahmad; Rayah Asiri; Emad Ali Alsaleh; Muhammad Imran; Mohammed Ali Kaddoura; Bilal Jawed; Narendar Kumar; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Unlocking ketone dimerization efficiency with multifunctional Zr and Hf based UiO-66 and NUS-6 MOFs: A synergy of experiment and theory - Muhammad Kashif Majeed; Rashid Iqbal; M.Umar Majeed; Muhammad Akram; M.Zeeshan Ashfaq; Adil Saleem (Fuel, 2026)

Harnessing Chromium-Resistant Bacteria from Tannery Wastewater: Innovative In Vitro and In Silico Strategies for Bioremediation - Hiba Ashfaq; Aatif Amin; Mohsin Tassawar Cheema; Muhammad Nouman Majeed (Water, Air, & Soil Pollution, 2026)

Silicon Role in Improving Leaf Physiology, Yield and Quality of Rice (Oryza Sativa L.) Under High Temperature Stress - Rania Baloch; Muhammad Farrukh Saleem; Muhammad Awais Arshad; Abdul Rehman; Aqsa Baloch; Muhammad Sarwar; Muhammad Ashfaq Wahid (Journal of Soil Science and Plant Nutrition, 2026)

Fabrication and In-Vitro Evaluation of Floating Tablets of Levofloxacin Hemihydrate for the Local Treatment of Helicobacter Pylori Infection - Abdullah Khan; Asif Nawaz; Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Haroon Khan; Muhammad Musa Khan; Irum Farooq; Saima Mahmood (Journal of Pharmaceutical Innovation, 2026)

Fabrication and In-Vitro and In-Vivo Assessment of Levofloxacin Beads Loaded Floating Tablets to improve Gastric Residence Time - Muhammad Israr; Kamran Ahmad Khan; Ashfaq Ahmad; Kifayat Ullah Shah; Naveed Ullah; Naheed Akhtar (Journal of Pharmaceutical Innovation, 2026)

Fabrication, Preparation and In-Vitro and In-Vivo Evaluation of Metoprolol Tartrate Controlled-Release Matrices to Establish a Correlation - Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Saima Mahmood; Sami-ul-Huq; Naveed Ullah; Anam Adil; Fida Muhammad (Journal of Pharmaceutical Innovation, 2026)

Mitigating salinity stress in wheat: employing biochemical parameters and stress tolerance index with foliar application of potassium and salicylic acid - Ilker Ugulu; Zafar Iqbal Khan; Farzana Shaheen; Muhammad Yasin Ashraf; Kafeel Ahmad; Muhammad Nadeem; Asma Ashfaq (Vegetos, 2026)

From roadside soil to cow milk: a potentially toxic metal transfer study using Pennisetum glaucum as fodder - Zafar Iqbal Khan; Natasha Ameer; Asma Ashfaq; Kafeel Ahmad; Muhammad Irfan Ashraf; Ijaz Rasool Noorka; Aima Iram Batool; Ilker Ugulu (Environmental Monitoring and Assessment, 2026)

Association of oral metoprolol exposure during heart failure hospitalization with death or readmission at 28-days and 6-months using a propensity score overlap-weighted EHR analysis - Azfar Athar Ishaqui; Emad Ali Alsaleh; Asaad Ahmed Asaad Khalil; Mohammed Ali Kaddoura; Khalid Orayj; Rayah Asiri; Sultan M. Alshahrani; Salman Ashfaq Ahmad; Narendar Kumar; Adnan Iqbal; Muhammad Bilal Maqsood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Comparative disproportionality signals for methotrexate monotherapy versus methotrexate combined with hydroxychloroquine, leflunomide, or sulfasalazine in rheumatoid arthritis: newly highlighted signals evaluated using drug information safety profiles - Azfar Athar Ishaqui; Khalid Orayj; Zeeshan Ahmed; Salman Ashfaq Ahmad; Sultan M. Alshahrani; Rayah Asiri; Adnan Iqbal; Asaad Ahmed Asaad Khalil; Mohammed Ali Kaddoura; Muhammad Bilal Maqsood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

CRISPR-Cas9 and next-generation gene editing strategies for therapeutic intervention of neurodegenerative pathways in Alzheimer’s disease: a state-of-the-art review - Muhammad Sohail Khan; Imran Zafar; Adil Jamal; Fayez Saeed Bahwerth; Samiullah Khan; Muhammad Faizan; Hanif Khan; Muhammad Noman; Kendrix Okeibunor; Ashfaq Ahmad; Muhammad Zain Ul Abedin (Acta Neurologica Belgica, 2026)

Navigating mobility in later life: How vehicle access and community context shape travel behaviour among older adults - Muhammad Adeel; Asad J. Khattak; Moetasim Ashfaq (Travel Behaviour and Society, 2026)

Artificial intelligence-driven surrogate modeling for computationally efficient and digitally decarbonized LNG process optimization under varying feed composition - Mahmoud Al-Mughairi; Ahmad Saeed; Ashfaq Ahmad; Muhammad Abdul Qyyum (Journal of Cleaner Production, 2026)

Optimisation of biomass-derived Propanol–Gasoline blends for sustainable bioenergy utilisation using response surface methodology - Muhammad Arslan Aslam; Ammar Hashmi; Muhammad Ashfaq; Muneeb-ur Rehman; Shah Nawaz Khan; Fakhar-ul Hasnain; Cheol Woo Park (Biomass and Bioenergy, 2026)

Evaluating the Accuracy of Machine Learning Models with Short-Term Lag Inputs for Univariate Daily Streamflow time Series Forecasting - Saad Ashfaq; Safia Waseem; Muhammad Tufail; Aqil Tariq (Water Resources Management, 2026)

Molecular evaluation of superior agronomic traits in local wheat germplasm using functional markers - Muhammad Qamar Ashfaq; Andleeb Anjum Qazalbash; Tayyaba Shaheen; Arzish Javaid; M. Qandeel Waheed; Anjuman Arif (Genetic Resources and Crop Evolution, 2026)

Radon concentration, its deterministic and probabilistic health risks through groundwater consumption, and spatial distribution - Said Muhammad; Fawad Hussain; Saeeda Yousaf; Zafar Iqbal; Umar Farooq; Ashfaq Ahmad (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Water Quality deterministic and Probabilistic Health Risks Assessment using Monte Carlo Simulation: Case Study from a Semi-Arid Region - Said Muhammad; Zeeshan Raza; Wajid Ali; Ashfaq Ahmad; Cem Tokatli; Imran Ud Din (Water, Air, & Soil Pollution, 2026)

Developing a RUSLE-Based Tool for Analyzing Climate Induced Soil Erosion and Reservoir Sedimentation in the Tarbela Region - Muhammad Arif Goheer; Sher Shah Hassan; Syeda Rosheen Raza Kazmi; Muhammad Taimoor Ashfaq Malik; Syed Zee Ali Shan (International Journal of Environmental Research, 2026)

Assessment of Chromium Toxicity and Health Risk in Vegetables Grown in Municipal Solid Waste-Amended Soils - Asma Ashfaq; Zafar Iqbal Khan; Toqeer Abbas; Saima Sadaf; Muhammad Arif; Muhammad Fayyaz; Iqra Parvez (Water, Air, & Soil Pollution, 2026)

Spatial distribution, source characterization, and risk indices of heavy metals pollution in the sediments of the Hindu Kush Lacustrine ecosystem - Said Muhammad; Zeeshan Ahmad; Cem Tokatli; Adnan Khan; Zafar Iqbal; Ashfaq Ahmad (Environmental Geochemistry and Health, 2026)

Investigating the Wound Healing Potential of CuCO3 Nanoparticles in Alloxan-Induced Diabetic Albino Mice: An Experimental and In Silico Approach - Muhammad Saqib Rafiq; Jabbir Ali Khan; Ashfaq Ahmad Shah Bukhari; Samra Shafqat; Ahmad Waheed; Muhammad Yasir Abbas; Muhammad Waseem Aslam; Imran Ibrahim Shaikh; Khalid S. Almaary; Muhammad Saleem Khan (Biological Trace Element Research, 2025)

Electrochemical energy storage systems: A review of types/functionalities, management systems and integration for real-life applications - Li-hua Ye; Josephine Baffoe; Eliasu Issaka; Yefan Shi; Hao Chen; Ai-ping Shi; Muhammad Muzamal Ashfaq (Next Research, 2025)

Arsenic Accumulation in Soil, Forage, and Milk Samples from Rainfed and Groundwater Irrigated Areas in Chakwal, Pakistan - Zafar Iqbal Khan; Asma Ashfaq; Sidra Khan; Kafeel Ahmad; Ijaz Rasool Noorka; Allah Bakhsh Gulshan; Shehnaz Fatima; Saqib Bashir; Saif Ullah; Muhammad Irfan Ashraf; Ilker Ugulu; Abdullah H. Alshahri (Bulletin of Environmental Contamination and Toxicology, 2025)

Heavy metals contamination of roadside dust, risk assessment, and their spatial distribution along the M-1 motorway - Sehrish Amin; Wajid Ali; Said Muhammad; Saeeda Yousaf; Ashfaq Ahmad; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Replacement of crop-residue silage for corn silage in feedlot buffalo - Muhammad Iqbal Anjum; Thiwakorn Ampapon; Shahbaz Javaid; Faisal Ashfaq; Metha Wanapat (Tropical Animal Health and Production, 2025)

Heavy metals contamination in water, soil, and potatoes in Sargodha and Sillanwali, Pakistan, with human health implications - Kafeel Ahmad; Mutiya Zafar; Zafar Iqbal Khan; Asma Ashfaq; Muhammad Mazhar Iqbal; Tayyaba Naz; Allah Ditta; Mashal Maqsood; Shahzad Akhtar; Ijaz Rasool Noorka (Environmental Monitoring and Assessment, 2025)

Eco-friendly synthesis of N-doped carbon quantum dots from Bombax ceiba stem: A photophysical study with exploratory sensing of Fe3+/Cd2+ and dye degradation - Muhammad Arslan Akhtar; Jalwa Anum; Sameh S. Ahmed; Muhammad Ashfaq Ahmed; Asad Muhammad Khan; Christie M. Sayes; Abdur Rahim (Journal of Water Process Engineering, 2025)

Spatial distribution, potential health risks, and sources of groundwater contamination in the semi-arid region - Owais Rabbani; Wajid Ali; Ghazanfar A. Khattak; Said Muhammad; Muhammad Nafees; Shahid Iqbal; Imran Ud Din; Ashfaq Ahmad; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Maize/Legume Intercropping Increases Nutrient Uptake, Crop Yields, Land Productivity, and Economic Profits in Resource-intensive Arid-irrigated Areas - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Ghulam Abbas Shah; Wang Zhiqi; Muhammad Jawad Hassan; Muhammad Bilal; Harun Gitari; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Silicon alleviates drought stress by up-regulating physiological and biochemical responses in two contrasting bread wheat cultivars - Waseem Ashfaq; Muhammad Kaleem; Graham Brodie; Sigfredo Fuentes; Alexis Pang; Dorin Gupta (Cereal Research Communications, 2025)
Drought stress (DS) substantially reduces plant growth and productivity in a rainfed cropping environment. Silicon (Si) has been recognized for its potential to alleviate the detrimental effects of various environmental stresses. However, its precise mechanisms in mitigating early growth DS and its impact on related physiological and biochemical attributes remain less understood. The present study, conducted in a glasshouse using a complete randomized design with four replications, was aimed to explore the role of pre-sowing Si treatment on two contrasting wheat cultivars (RAC875, drought-tolerant; Kukri, drought-susceptible) in mitigating the physiological and biochemical disruptions induced by early growth DS (14 days at 38 ± 3% pot field capacity). The results showed that Si treatment significantly increased the number of productive tillers and fresh weight in both cultivars under DS. Compared to the control (DS without Si treatment), Si treatment significantly enhanced chlorophyll content (RAC875, 8.7%; Kukri, 12.7%), relative water content (RAC875, 10.8%; Kukri, 18.1%), and chlorophyll fluorescence (RAC875, 10.1%; Kukri, 22.3%) under DS conditions. Additionally, Si treatment increased total soluble sugars, fructose content, and free amino acids while reducing proline content and lipid peroxidation concentrations in both cultivars under DS. Moreover, Si treatment significantly boosted cellular antioxidant activities, including ascorbate peroxidase (RAC875, 11.3%; Kukri, 9.2%), catalase (RAC875, 22.2%; Kukri, 25.5%), and peroxidase (RAC875, 19%; Kukri, 15.8%) under DS. Overall, these results show that Si effectively alleviates early growth DS by up-regulating antioxidants, osmoprotectants, and the photochemical process, thereby improving plant growth and productivity through enhanced photosynthesis.

DusVax: a universal pan-viral multi-epitope vaccine (PV-MEV) for pandemic preparedness against ten high-priority viral pathogens - Allah Rakha Yaseen; Muhammad Suleman; Mahrukh Afzal; Hania Usama; Warda Ashfaq; Sehrish Firyal; Ayesha Arif; Amna Latif; Ali Asghar; Abdul Salam Qadri (The Nucleus, 2025)

Toxicological risk assessment and sources of heavy metal(loid)s using compositional data analysis, Astore River Basin, Himalaya - Wajid Ali; Said Muhammad; Cem Tokatli; Ashfaq Ahmad; Zhang Luyuan (Marine Pollution Bulletin, 2025)

Impacts of sea level rise and climate change on the sources, preservation and thermal stability of sedimentary organic carbon in the East China Sea inner shelf since the last deglaciation - Muhammad Faheem Ashfaq; Bin Zhao; Lilei Chen; Yang Ding; Nan Wang; Xiwen Ye; Chao Gao; Xiaoyong Duan; Peng Yao (Quaternary Science Reviews, 2025)

Flood susceptibility assessment and mapping using GIS-based analytical hierarchy process and frequency ratio models - Saad Ashfaq; Muhammad Tufail; Asif Niaz; Sher Muhammad; Hassan Alzahrani; Aqil Tariq (Global and Planetary Change, 2025)

Sustainable water management practice in South Asian Countries: The importance of water resources, temperature, and bioenergy on ecological footprint - Muhammad Haroon Shah; Syed Tauseef Hassan; Irfan Ullah; Yaoyao Wang; Ashfaq Ahmad Shah (Gondwana Research, 2025)

Investigation of the genesis and intensification of simultaneous cyclones in the Arabian sea and Bay of Bengal in November 2020 - Abhishek Kumar; Arun Chakraborty; Mansour Almazroui; Muhammad Mubashar Dogar; Irfan Ur Rashid; Muhammad Adnan Abid; Moetasim Ashfaq (Theoretical and Applied Climatology, 2025)

Data-driven multi-hazard susceptibility and community perceptions assessment using a mixed-methods approach - Muhammad Hussain; Kashif Ullah; Muhammad Tayyab; Safi Ullah; Ashfaq Ahmad Shah; Jiquan Zhang; Zhijun Tong; Xingpeng Liu; Zahid Ur Rahman (Journal of Environmental Management, 2025)

Multivariate analysis of potential health hazards of manganese via dietary exposure of widely consumed vegetables amended with municipal solid waste - Asma Ashfaq; Zafar Iqbal Khan; Kafeel Ahmad; Hamid Raza; Muhammad Nazim; Ajaz Ahmad (Environmental Geochemistry and Health, 2025)

Importance of an Oncology Interest Group in Medical School: Experience from a Developing Country - Hammad Atif Irshad; Abdul Rehman; Muhammad Ali Akbar Khan; Dahir Ashfaq; Munira Moosajee (Journal of Cancer Education, 2025)

Spatial distribution of hazard index via heavy metals consumption in water from the himalayan lacustrine ecosystems - Said Muhammad; Tauseef Ahmed; Sehrish Amin; Cem Tokatli; Fikret Ustaoğlu; Ashfaq Ahmad; Wajid Ali; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Physicochemical, Enzymatic, and Microbial Responses to Phosphofructokinase Overexpressing Transgenic Potato Cultivation: A Pot Experiment - Muhammad Junaid Sadiq Gill; Umer Ali; Aqib Hassan Ali Khan; Ismat Nawaz; Tayyab Ashfaq Butt; Cyrus Raza Mirza; Ameena Iqbal; Arfan Ali; Faiz Ur Rahman; Sohail Yousaf; Mazhar Iqbal (American Journal of Potato Research, 2025)

Using DNA metabarcoding to assess insect diversity in grasslands - Changjin Lin; Haibin Han; Kejian Lin; Hongmei Cheng; Luyao Fu; Muhammad Ashfaq; Paul D. N. Hebert; Chenxi Liu (Applied Entomology and Zoology, 2025)

Recovery and treatment of cooling tower blowdown water: Challenges, recent advancement, and future perspectives - Syed Taufiq Ahmad; Ashfaq Ahmad; Rizwan Ahmad; Ahmed Fuwad; Azeem Mushtaq; Muhammad Kashif Shahid (Journal of Environmental Chemical Engineering, 2025)

Retraction Note: Evaluation of toxicity potential of cobalt in wheat irrigated with wastewater: health risk implications for public - Fu Chen; Zafar Iqbal Khan; Asma Zafar; Jing Ma; Muhammad Nadeem; Kafeel Ahmad; Shehzadi Mahpara; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; et al. (Environmental Science and Pollution Research, 2025)

Enhanced microwave absorption and improved broadband with synergistic effect of nest like self-assembly of CoFe2O4/Co3O4 heterostructured composites - M. Zeeshan Ashfaq; Aamna Ashfaq; Xingxing Cheng; Hongyu Gong; Adil Saleem; Rashid Iqbal; Muhammad Sajjad; Junbin Lu; M. Mamoor; Muhammad K. Majeed (Chemical Engineering Journal, 2025)

Biochars Induced Changes in CO2 Evolution and Biochemical Properties of an Alkaline Subtropical soil - Tayyba Kanwal Choudhary; Khalid Saifullah Khan; Qaiser Hussain; Muhammad Ashfaq; Choudhary Muhammad Saqlain (Journal of Soil Science and Plant Nutrition, 2025)

Radon contamination, risk evaluation, and their spatial distribution in groundwater of three selected northern districts - Said Muhammad; Rizwan Ullah; Sehrish Amin; Ashfaq Ahmad (Journal of Geochemical Exploration, 2025)

Spatial distribution of groundwater quality and risk indices evaluation via consumption - Said Muhammad; Rizwan Ullah; Sehrish Amin; Haseeb Haroon; Ashfaq Ahmad (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Two-dimensional Bi2Se3 nanosheets synthesis for efficient electrocatalytic production of ammonia from nitrate - Sadeeq Ullah; Aftab Ahmad; Majeed Ur Rehman; Ashfaq Ahmad; Shah Zada; Daxiang Cui; Hafiz Muhammad Adeel Sharif; Lu Li (Journal of Environmental Chemical Engineering, 2024)

Correction to: Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Spatial distribution of heavy metal contamination and risk indices of surface sediments in high-altitude lakes - Said Muhammad; Tauseef Ahmed; Rizwan Ullah; Cem Tokatli; Ashfaq Ahmad (Environmental Monitoring and Assessment, 2024)

Flexible temperature and humidity sensors of plants for precision agriculture: Current challenges and future roadmap - Muhammad Ikram; Sikander Ameer; Fnu Kulsoom; Mazhar Sher; Ashfaq Ahmad; Azlan Zahid; Young Chang (Computers and Electronics in Agriculture, 2024)

Synergistic biochar and Serratia marcescens tackle toxic metal contamination: A multifaceted machine learning approach - Hamid Rehman; Aqib Hassan Ali Khan; Tayyab Ashfaq Butt; Muhammad Toqeer; Muhammad Bilal; Mahtab Ahmad; Ahmed Abdullah Alawi Al-Naghi; Enamur Rahim Latifee; Omar Ali Saad Algassem; Mazhar Iqbal (Journal of Environmental Management, 2024)

Correction: Spatial distribution of physicochemical parameters and drinking and irrigation water quality indices in the Jhelum River - Tofeeq Ahmad; Said Muhammad; Muhammad Umar; Muhammad Usman Azhar; Alaa Ahmed; Ashfaq Ahmad; Rizwan Ullah (Environmental Geochemistry and Health, 2024)

Predictability of the early summer surface air temperature over Western South Asia - Irfan Ur Rashid; Muhammad Adnan Abid; Marisol Osman; Fred Kucharski; Moetasim Ashfaq; Antje Weisheimer; Mansour Almazroui; José Abraham Torres-Alavez; Muhammad Afzaal (Climate Dynamics, 2024)
Variability of the Surface Air Temperature (SAT) over the Western South Asia (WSA) region leads to frequent heatwaves during the early summer (May-June) season. The present study uses the European Centre for Medium-Range Weather Forecast’s fifth-generation seasonal prediction system, SEAS5, from 1981 to 2022 based on April initial conditions (1-month lead) to assess the SAT predictability during early summer season. The goal is to evaluate the SEAS5’s ability to predict the El Niño-Southern Oscillation (ENSO) related interannual variability and predictability of the SAT over WSA, which is mediated through upper-level (200-hPa) geopotential height anomalies. This teleconnection leads to anomalously warm surface conditions over the region during the negative ENSO phase, as observed in the reanalysis and SEAS5. We evaluate SEAS5 prediction skill against two observations and three reanalyses datasets. The SEAS5 SAT prediction skill is higher with high spatial resolution observations and reanalysis datasets compared to the ones with low-resolution. Overall, SEAS5 shows reasonable skill in predicting SAT and its variability over the WSA region. Moreover, the predictability of SAT during La Niña is comparable to El Niño years over the WSA region.

Emerging trends in algae farming on non-arable lands for resource reclamation, recycling, and mitigation of climate change-driven food security challenges - Fatima Tahir; Hira Ashfaq; Aqib Zafar Khan; Mahwish Amin; Iqra Akbar; Hafiza Aroosa Malik; Mohammed Abdullah; Abdulrahman H. Alessa; Ahmad A. Alsaigh; Peter J. Ralph; Muhammad Aamer Mehmood; Sana Malik (Reviews in Environmental Science and Bio/Technology, 2024)

Cenchrus ciliaris L. ameliorates cigarette-smoke induced acute lung injury by reducing inflammation and oxidative stress - Muhammad Irfan Aslam; Saad Touqeer; QurratUlAin Jamil; Muhammad Irfan Masood; Adeel Sarfraz; Shafaat Yar Khan; Muhammad Saeed Jan; Sulaiman Mohammed Abdullah Alnasser; Ashfaq Ahmad; Fatima Aslam; Shahid Muhammad Iqbal (South African Journal of Botany, 2024)

Spatial distribution of physicochemical parameters and drinking and irrigation water quality indices in the Jhelum River - Tofeeq Ahmad; Said Muhammad; Muhammad Umar; Muhammad Usman Azhar; Alaa Ahmed; Ashfaq Ahmad; Rizwan Ullah (Environmental Geochemistry and Health, 2024)

Numerical investigation of vortex-induced vibrations (VIV) of a rotating cylinder in in-line and cross-flow directions subjected to oscillatory flow - Ubaid Ur Rehman; Adnan Munir; Niaz Bahadur Khan; Ming Zhao; Muhammad Kashif; Mohammad S. Islam; Zeeshan Saeed; Mian Ashfaq Ali (Ocean Engineering, 2024)

Spatial distribution of drinking, irrigation water quality, and health risk indices of high-altitude lakes - Said Muhammad; Aasim Zeb; Rizwan Ullah; Sehrish Amin; Ashfaq Ahmad; Cem Tokatli (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Advanced strategies to mitigate heavy metals in ground and sewage water - Muhammad Mahmood Ahmed; Tuba Tariq; Mirza Abid Mehmood; Muhammad Ashfaq; Murtaza Hasan (Current Opinion in Green and Sustainable Chemistry, 2024)

Evaluation of irrigation, drinking, and risk indices for water quality parameters of alpine lakes - Rizwan Ullah; Said Muhammad; Wajid Ali; Sehrish Amin; Sardar Khan; Atta Rasool; Abd El-Latif Hesham; Muhammad Umar; Shaukat Ali; Shahid Iqbal; Ashfaq Ahmad (Environmental Geochemistry and Health, 2024)

Renewable energy and green economic growth nexus: Insights from simulated dynamic ARDL - Saira Ashfaq; Song Liangrong; Fahad Waqas; Saqib Gulzar; Ghulam Mujtaba; Rana Muhammad Nasir (Gondwana Research, 2024)

Advanced network pharmacology and molecular docking-based mechanism study to explore the multi-target pharmacological mechanism of Cymbopogon citratus against Alzheimer's disease - Kinza Fatima; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Muhammad Asif; Asma Haque; Muhammad Qasim; Mubarak A. Alamri; Ziyad Tariq Muhseen; Fatima Noor; Muhammad Sadaqat (South African Journal of Botany, 2024)

Synthesis of N-doped TiO2 nanoparticles with enhanced photocatalytic activity for 2,4-dichlorophenol degradation and H2 production - Javed Ali Khan; Murtaza Sayed; Noor S. Shah; Sanaullah Khan; Ashfaq Ahmad Khan; Muhammad Sultan; Ammar M. Tighezza; Jibran Iqbal; Grzegorz Boczkaj (Journal of Environmental Chemical Engineering, 2023)

Systematic elucidation of the multi-target pharmacological mechanism of Terminalia arjuna against congestive cardiac failure via network pharmacology and molecular modelling approaches - Aqsa Asghar; Muhammad Qasim; Fatima Noor; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Muhammad Shareef Masoud; Rashid Bhatti; Ahmad Almatroudi; Faris Alrumaihi; Khaled S. Allemailem (Natural Product Research, 2023)

Blockchain-enabled smart agriculture: Enhancing data-driven decision making and ensuring food security - Khalil Ur Rehman; Shahla Andleeb; Maryam Ashfaq; Nida Akram; Muhammad Waqar Akram (Journal of Cleaner Production, 2023)

Moisture sources for precipitation variability over the Arabian Peninsula - Matthew F. Horan; Fulden Batibeniz; Fred Kucharski; Mansour Almazroui; Muhammad Adnan Abid; Joshua S. Fu; Moetasim Ashfaq (Climate Dynamics, 2023)
We apply the Lagrangian-based moisture back trajectory method to two reanalysis datasets to determine the moisture sources for wet season precipitation over the Arabian Peninsula, defined as land on the Asian continent to the south of the Turkish border and west of Iran. To accomplish this, we make use of the evaporative source region between 65°W–120°E and 30°S–60°N, which is divided into twelve sub-regions. Our comparison of reanalyses and multiple observations allows us to validate datasets and highlight broad-scale similarities in characteristics, notwithstanding some inconsistencies in the southwest AP. The results indicate north-to-south spatiotemporal heterogeneity in the characteristics of dominant moisture sources. In the north, moisture for precipitation is mainly sourced from midlatitude land and water bodies, such as the Mediterranean and Caspian Seas. Areas further south are dependent on moisture transport from the Western Indian Ocean and parts of the African continent. The El Niño-Southern Oscillation (ENSO) exhibits an overall positive but sub-seasonally varying influence on the precipitation variability over the region, with noticeable moisture anomalies from all major source regions. A significant drying trend exists over parts of the Peninsula, which both reanalyses partially attribute to anomalies in the moisture advection from the Congo Basin and South Atlantic Ocean. However, considerable uncertainty in evaporation trends over the terrestrial evaporative sources in observations warrants additional modeling studies to further our understanding of key processes contributing to the negative trends.

Validation of the environmental Kuznets curve and role of economic globalization: an aggregate and sectoral analysis of an Indian economy - Ashfaq Ahmad; Muhammad Mobeen Shafqat; Muhammad Ilyas; Muhammad Umair Ashraf; Afshan Urooj; Zhao Yu huan (Air Quality, Atmosphere & Health, 2023)

The Dynamics of the Relationship Between Water Availability, Water Equity, Economic Benefits and Water User Associations’ Performance: A PLS-SEM Approach - Mohsin Riaz; Muhammad Ashfaq; Ismet Boz; Pomi Shahbaz (Water Resources Management, 2023)

Correction: KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)

Green investment, institutional quality, and environmental performance: evidence from G-7 countries using panel NARDL approach - Jiguo Zhao; Saif ur Rahman; Sahar Afshan; Muhammad Sibt E. Ali; Hammad Ashfaq; Sadia Idrees (Environmental Science and Pollution Research, 2023)

Hydrogen Peroxide Promotes Terminal Heat Stress Recovery in Wheat by Strengthening Leaf Physiological Functioning - Muhammad Sarwar; Muhammad Farrukh Saleem; Siraj Ahmed; Hamza Maqsood; Saddam Hussain; Muhammad Ashfaq Wahid; Muhammad Kashif Munir; Muhammad Zafar; Najeeb Ullah; Ali Khoddami (Journal of Plant Growth Regulation, 2023)

KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)
Super Basmati is an elite variety with extra-long grains and superior quality but its yield is severely affected by water stress. Recombinant inbred lines (RILs) developed from the cross of Super Basmati and IR55419-04 (a coarse grained variety with high yield potential) were used to identify and map yield-related quantitative trait loci (QTLs) under normal field conditions. Genotypes for 244 KASP markers were obtained from 188 F 9 RILs and a linkage map constructed of 1369.4 cM, with average marker interval of 10.5 cM. Eleven agronomic traits were phenotyped in RILs and parents. Composite interval mapping and inclusive composite interval mapping model identified 21 common QTLs related to nine agronomic traits; of the QTLs identified, twelve mapped at novel positions. LOD scores ranged from 2.51 for number of filled grains ( qFG1.1 ) to 16.8 for plant height ( qPH1.1 ). Four major effect QTLs could explain 20% of variation related for plant height, hundred-grain weight and grain width. Alleles from IR55419-04 improved grain filling, grain weight and grain width, while alleles from Super Basmati contributed to longer grains, panicles and flag leaves. Putative candidate genes were identified for 18 yield-related QTLs. These results validate the use of KASP genotyping for QTL mapping of yield-related traits in a bi-parental segregating population. SNPs in the QTLs identified in this study can be used in marker assisted selection for yield components to improve Basmati rice.

Occurrence and risk evaluation of endocrine-disrupting chemicals in wastewater and surface water of Lahore, Pakistan - Muhammad Ashfaq; Yan Li; Muhammad Zubair; Muhammad Saif Ur Rehman; Sajjad Hussain Sumrra; Muhammad Faizan Nazar; Ghulam Mustafa; Muhammad Tahir Fazal; Humayun Ashraf; Qian Sun (Environmental Geochemistry and Health, 2023)

Valorization of palm tree (Phoenix dactylifera L.) leaves from harsh weather climate by silage using endogenous lactic acid bacteria, and application of MALDI-TOF MS for study of populations dynamics - Muhammad Zaid Jawaid; Mohammad Yousaf Ashfaq; Mohammad Al-Ghouti; Nabil Zouari (Bioresource Technology Reports, 2023)

Modulations Induced by Seed Priming of Strigolactone (GR24) in Morpho-Physiological and Biochemical Attributes of Ajwain (Trachyspermum ammi L.) Under Salt Stress - Nazoora Mujahid; Muhammad Shahbaz; Aysha Kiran; Muhammad Ashfaq Wahid (Journal of Plant Growth Regulation, 2023)

Manipulation of plant growth stimulants on plant morphology, phenology, and disease incident of Gossypium hirsutum L. under various thermal regimes - Muhammad Sarwar; Muhammad Farrukh Saleem; Basharat Ali; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Ashfaq Wahid; Muhammad Shahid; Theodore M. Mwamba; Bilal Ahmad Khan; Hamza Maqsood (Arabian Journal of Geosciences, 2023)

Effects of age, body weight, semen collection frequency and holding duration on semen traits of broiler breeder reared under different housing systems - Muhammad Shabir Shaheen; Sadaf Aslam; Shahid Mehmood; Muhammad Tariq; Yassar Abbas; Hassan Ashfaq; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Prospects of antimicrobial peptides as an alternative to chemical preservatives for food safety - Iqra Kamal; Usman Ali Ashfaq; Sumreen Hayat; Bilal Aslam; Muhammad Hassan Sarfraz; Hamna Yaseen; Muhammad Shahid Riaz Rajoka; Asad Ali Shah; Mohsin Khurshid (Biotechnology Letters, 2023)

Invasive success of Ipomoea carnea Jacq. through plasticity in physio-anatomical and phytochemical traits across diversified habitats - Syed Mohsan Raza Shah; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Muhammad Ashfaq Wahid (Biological Invasions, 2023)

Urban Heat Island vulnerability mapping using advanced GIS data and tools - Paras Sidiqui; Phillip B Roös; Murray Herron; David S Jones; Emma Duncan; Ali Jalali; Zaheer Allam; Bryan J Roberts; Alexander Schmidt; Muhammad Atiq Ur Rehman Tariq; Ashfaq Ahmed Shah; Nasir Abbas Khan; et al. (Journal of Earth System Science, 2022)

Genome wide association mapping of yield and various desirable agronomic traits in Rice - Muhammad Ashfaq; Abdul Rasheed; Muhammad Sajjad; Muhammad Ali; Bilal Rasool; Muhammad Arshad Javed; Sami Ul Allah; Shabnum Shaheen; Alia Anwar; Muhammad Shafiq Ahmad; Urooj Mubashar (Molecular Biology Reports, 2022)

Estimation of economic, environmental, and social efficiency for sustainable development in G-8 and SAARC countries: a data envelopment analysis - Qamar Ali; Sofia Anwar; Muhammad Tariq Iqbal Khan; Muhammad Rizwan Yaseen; Muhammad Ashfaq (Environmental Science and Pollution Research, 2022)

Bisphenol S induced dysregulations in liver; iron regulatory genes and inflammatory mediators in male Wistar rats - Shazia Ghafoor; Muddasir Hassan Abbasi; Muhammad Babar Khawar; Asima Tayyeb; Tayyaba Saleem; Isbah Ashfaq; Nadeem Sheikh (Environmental Science and Pollution Research, 2022)

Effects of maize silage substitution with sugarbeet or citrus pulp ensiled with corncobs on growth performance, digestibility, and economic benefits in buffalo calves - Muhammad Iqbal Anjum; Shahbaz Javaid; Faisal Ashfaq; Javed Iqbal (Tropical Animal Health and Production, 2022)

Bioaccumulation and Health Risk Assessment of Heavy Metal (loid)s in Different Fish Species of Hainan Island, China - Tauseef Ahmad; Sumaira Gul; Muhammad Amjad Khan; Xiaoping Diao; Ashfaq Ahmad; Shakil Ahmad (Thalassas: An International Journal of Marine Sciences, 2022)

Production of a high molecular weight levan by Bacillus paralicheniformis, an industrially and agriculturally important isolate from the buffalo grass rhizosphere - Anam Nasir; Waqar Ahmad; Fazal Sattar; Iram Ashfaq; Stephen R. Lindemann; Ming-Hsu Chen; Wim Van den Ende; Ebru Toksoy Ӧner; Onur Kirtel; Shazia Khaliq; Muhammad A. Ghauri; Munir A. Anwar (Antonie van Leeuwenhoek, 2022)

Assessment of land use/land cover changes and its effect on land surface temperature using remote sensing techniques in Southern Punjab, Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Hamid Majeed; Saeed Ahmad Qaisrani; Hafiz Mohkum Hammad; Muhammad Amjad; Iftikhar Ahmad; Shah Fahad; Naveed Ahmad; Wajid Nasim (Environmental Science and Pollution Research, 2022)

Imaging of rupture process of 2005 Mw 7.6 Kashmir earthquake using back projection techniques - Mahmood Sultan; Farhan Javed; Muhammad Fahad Mahmood; Muhammad Ali Shah; Khawar Ashfaq Ahmed; Talat Iqbal (Arabian Journal of Geosciences, 2022)

Dihydroquinazolin-4(1H)-one derivatives as novel and potential leads for diabetic management - Oluwatoyin Babatunde; Shehryar Hameed; Uzma Salar; Sridevi Chigurupati; Abdul Wadood; Ashfaq Ur Rehman; Vijayan Venugopal; Khalid Mohammed Khan; Muhammad Taha; Shahnaz Perveen (Molecular Diversity, 2022)

Quantitative evaluation of zinc metal in meadows and ruminants for health assessment: implications for humans﻿ - Ayesha Maqsood; Zafar Iqbal Khan; Kafeel Ahmad; Shahzad Akhtar; Asma Ashfaq; Ifra Saleem Malik; Razia Sultana; Muhammad Nadeem; Jawaher Alkahtani; Yheni Dwiningsih; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Sustainability and efficiency analysis w.r.t adoption of climate-smart agriculture (CSA) in Pakistan: a group-wise comparison of adopters and conventional farmers - Muhammad Ali Imran; Asghar Ali; Richard J. Culas; Muhammad Ashfaq; Irfan Ahmad Baig; Shoaib Nasir; Arshad Hussain Hashmi (Environmental Science and Pollution Research, 2022)

Climate change impact uncertainty assessment and adaptations for sustainable maize production using multi-crop and climate models - Mubashra Yasin; Ashfaq Ahmad; Tasneem Khaliq; Muhammad Habib-ur-Rahman; Salma Niaz; Thomas Gaiser; Iqra Ghafoor; Hafiz Suboor ul Hassan; Muhammad Qasim; Gerrit Hoogenboom (Environmental Science and Pollution Research, 2022)
Future climate scenarios are predicting considerable threats to sustainable maize production in arid and semi-arid regions. These adverse impacts can be minimized by adopting modern agricultural tools to assess and develop successful adaptation practices. A multi-model approach (climate and crop) was used to assess the impacts and uncertainties of climate change on maize crop. An extensive field study was conducted to explore the temporal thermal variations on maize hybrids grown at farmer’s fields for ten sowing dates during two consecutive growing years. Data about phenology, morphology, biomass development, and yield were recorded by adopting standard procedures and protocols. The CSM-CERES, APSIM, and CSM-IXIM-Maize models were calibrated and evaluated. Five GCMs among 29 were selected based on classification into different groups and uncertainty to predict climatic changes in the future. The results predicted that there would be a rise in temperature (1.57–3.29 °C) during the maize growing season in five General Circulation Models (GCMs) by using RCP 8.5 scenarios for the mid-century (2040–2069) as compared with the baseline (1980–2015). The CERES-Maize and APSIM-Maize model showed lower root mean square error values (2.78 and 5.41), higher d -index (0.85 and 0.87) along reliable R 2 (0.89 and 0.89), respectively for days to anthesis and maturity, while the CSM-IXIM-Maize model performed well for growth parameters (leaf area index, total dry matter) and yield with reasonably good statistical indices. The CSM-IXIM-Maize model performed well for all hybrids during both years whereas climate models, NorESM1-M and IPSL-CM5A-MR, showed less uncertain results for climate change impacts. Maize models along GCMs predicted a reduction in yield (8–55%) than baseline. Maize crop may face a high yield decline that could be overcome by modifying the sowing dates and fertilizer (fertigation) and heat and drought-tolerant hybrids.

Biochemical resistance characterization to chlorpyrifos, acetamiprid, spinosad, and emamectin benzoate in Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) from Pakistan - Bushra Saddiq; Muhammad Babar Shahzad Afzal; Ashfaq Ahmad Sial; Naeem Abbas; Sarfraz Ali Shad; Asif Sajjad; Sajjad Ali (Phytoparasitica, 2022)

Genotypic Differences Among the Rice Genotypes to Arsenic Stress Cultivated Under Two Water Regimes: With an Inference to Human Health - Hafiz Faiq Bakhat; Sidra Arshad; Natasha; Sunaina Abbas; Ghulam Mustafa Shah; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Sajjad; Muhammad Ashfaq; Muhammad Shahid (Journal of Plant Growth Regulation, 2022)

Production of bimodal molecular weight levan by a Lactobacillus reuteri isolate from fish gut - Waqar Ahmad; Anam Nasir; Fazal Sattar; Iram Ashfaq; Ming-Hsu Chen; Azam Hayat; Mujaddad ur Rehman; Sainan Zhao; Shazia Khaliq; Muhammad Afzal Ghauri; Munir Ahmad Anwar (Folia Microbiologica, 2022)

Correction to: Bioaccumulation of lead in different varieties of wheat plant irrigated with wastewater in remote agricultural regions - Wuyi Liu; Asma Zafar; Zafar Iqbal Khan; Muhammad Nadeem; Kafeel Ahmad; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq (Environmental Science and Pollution Research, 2022)

Ecological risk assessment of heavy metal chromium in a contaminated pastureland area in the Central Punjab, Pakistan: soils vs plants vs ruminants - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Nadeem; Shahid Mahmood; Muhammad Umar Farooq Awan; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Ayesha Maqsood; et al. (Environmental Science and Pollution Research, 2022)

Evaluation of potential ecological risk and prediction of zinc accumulation and its transfer in soil plants and ruminants: public health implications - Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Asma Ashfaq; Razia Sultana; Fatima Ghulam Muhammad; Ayesha Maqsood; Majida Naeem; Ifra Saleem Malik; Mudasra Munir; et al. (Environmental Science and Pollution Research, 2022)

Bioaccumulation and transfer of zinc in soil plant and animal system: a health risk assessment for the grazing animals - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Majida Naeem; Muhammad Nadeem; Jing Ma; Muhammad Umer Farooq Awan; Shahzadi Mahpara; Shahid Mehmood (Environmental Science and Pollution Research, 2022)

Implementation of Vaccinomics and In-Silico Approaches to Construct Multimeric Based Vaccine Against Ovarian Cancer - Muhammad Sufyan; Farah Shahid; Faiza Irshad; Anam Javaid; Muhammad Qasim; Usman Ali Ashfaq (International Journal of Peptide Research and Therapeutics, 2021)

Foliar Spray of Natural and Synthetic Plant Growth Promoters Accelerates Growth and Yield of Cotton by Modulating Photosynthetic Pigments - Muhammad Shaukat; Ashfaq Ahmad; Tasneem Khaliq; Irfan Afzal; Sher Muhammad; Bushra Safdar; Sabir Hussain Shah (International Journal of Plant Production, 2021)

Farm-level autonomous adaptation to climate change and its impact on crop productivity: evidence from Pakistan - Nasir Abbas Khan; Zaiwu Gong; Ashfaq Ahmad Shah; Muhammad Abid; Uttam Khanal (Environment, Development and Sustainability, 2021)

Using space–time scan statistic for studying the effects of COVID-19 in Punjab, Pakistan: a guideline for policy measures in regional agriculture - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Shah Fahad; Wajid Nasim; Hafiz Mohkum Hammad; Ghulam Mustafa Shah; Behzad Murtaza; Muhammad Tahir; Saima Parveen (Environmental Science and Pollution Research, 2021)

Impacts of climate change on yield of cereal crops in northern climatic region of Pakistan - Inayatullah Jan; Muhammad Ashfaq; Abbas Ali Chandio (Environmental Science and Pollution Research, 2021)

Evaluation of pasture allowance of manganese for ruminants - Xiaoping Ge; Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Mudasra Munir; Muhammad Nadeem; Muhammad Umer Farooq Awan; et al. (Environmental Science and Pollution Research, 2021)

Inhibition of jack bean urease by amphiphilic peptides - Zafar Ali Shah; Sadam Hussain; Serab Khan; Nawab Ali; Samiullah Burki; Syed Uzair Ali Shah; Ashfaq Ahmad; Faiz -Ur-Rehman; Muhammad Nasimullah Qureshi; Syed Muhammad Mukrram Shah; Farzana Shaheen (Medicinal Chemistry Research, 2021)

Livelihood diversification in managing catastrophic risks: evidence from flood-disaster regions of Khyber Pakhtunkhwa Province of Pakistan - Ashfaq Ahmad Shah; Zaiwu Gong; Nasir Abbas Khan; Imran Khan; Muhammad Ali; Syed Asif Ali Naqvi (Environmental Science and Pollution Research, 2021)

Evaluation of transfer of lead in soil plant animal system: assessment of consequences of its toxicity - Fu Chen; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Tasneem Ahmad; Ifra Saleem Malik; Asma Ashfaq; Mudasra Munir; Sonaina Nazar; Zunaira Munir; Abid Ejaz; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

Nutrient Availability to Maize Crop (Zea mays L.) in Biochar Amended Alkaline Subtropical Soil - Tayyba Kanwal Choudhary; Khalid Saifullah Khan; Qaiser Hussain; Muhammad Ashfaq (Journal of Soil Science and Plant Nutrition, 2021)

Correction to: Monitoring of copper accumulation in water, soil, forage, and cows impacted by heavy automobiles - Tasneem Ahmad; Sonaina Nazar; Kafeel Ahmad; Zafar Iqbal Khan; Humayun Bashir; Asma Ashfaq; Mudasra Munir; Zunaira Munir; Khadim Hussain; Jawaher Alkahtani; Mohamed Soliman Elshikh; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

Climate change impact assessment, flood management, and mitigation strategies in Pakistan for sustainable future - Imran Khan; Hongdou Lei; Ashfaq Ahmad Shah; Inayat Khan; Ihsan Muhammad (Environmental Science and Pollution Research, 2021)

Monitoring of copper accumulation in water, soil, forage, and cows impacted by heavy automobiles in Sargodha, Pakistan - Tasneem Ahmad; Sonaina Nazar; Kafeel Ahmad; Zafar Iqbal Khan; Humayun Bashir; Asma Ashfaq; Mudasra Munir; Zunaira Munir; Khadim Hussain; Jawaher Alkahtani; Mohamed Soliman Elshikh; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Evaluation of toxicity potential of cobalt in wheat irrigated with wastewater: health risk implications for public - Fu Chen; Zafar Iqbal Khan; Asma Zafar; Jing Ma; Muhammad Nadeem; Kafeel Ahmad; Shehzadi Mahpara; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; et al. (Environmental Science and Pollution Research, 2021)

Investigating the effect of Aspergillus niger inoculated press mud (biofertilizer) on the potential of enhancing maize (Zea mays L.) yield, phosphorous use efficiency, and phosphorous agronomic efficiency - Urooj Naeem; Muhammad Afzaal; Irfan ul Haq; Akram Qazi; Abdullah Yasar; Amtul Bari Tabinda; Yusra Mahfooz; Asad Ullah Naz; Humera Aslam Awan; Ashfaq Ahmad (Arabian Journal of Geosciences, 2021)

Biochemically Triggered Heat and Drought Stress Tolerance in Rice by Proline Application - Sajid Hanif; Muhammad Farrukh Saleem; Muhammad Sarwar; Muhammad Irshad; Abdul Shakoor; Muhammad Ashfaq Wahid; Haroon Zaman Khan (Journal of Plant Growth Regulation, 2021)

Synthesis, urease inhibition screening and molecular docking studies of piperonal based imine derivatives - Obaid-ur-Rahman Abid; Saima Daud; Asma Sardar; Wajid Rehman; Abdul Wadood; Ashfaq Ur Rehman; Toheed Akhter; Iram Bibi; Zaheer Ahmad; Muhammad Yasir (Medicinal Chemistry Research, 2021)

Mapping farmers’ vulnerability to climate change and its induced hazards: evidence from the rice-growing zones of Punjab, Pakistan - Nasir Abbas Khan; Qijie Gao; Muhammad Abid; Ashfaq Ahmad Shah (Environmental Science and Pollution Research, 2021)

Bioaccumulation of cadmium in different genotypes of wheat crops irrigated with different sources of water in agricultural regions - Asma Zafar; Zafar Iqbal Khan; Wuyi Liu; Humayun Bashir; Kafeel Ahmad; Kinza Wajid; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Muhammad Nadeem; Tasneem Ahmad; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2021)

Landslides assessment using geophysical and passive radon exhalation detection techniques in Murree Hills, northern Pakistan: Implication for environmental hazard assessment - Khawar Ashfaq Ahmed; Sarfraz Khan; Mahmood Sultan; Umair Bin Nisar; Muhammad Rizwan Mughal; Shahid Nadeem Qureshi (Journal of Earth System Science, 2020)

Measuring education sector resilience in the face of flood disasters in Pakistan: an index-based approach - Ashfaq Ahmad Shah; Zaiwu Gong; Muhammad Ali; Ali Jamshed; Syed Asif Ali Naqvi; Shaista Naz (Environmental Science and Pollution Research, 2020)

Evaluation of rapid polymyxin Nordmann Poirel test for detection of polymyxin resistance in clinical isolates of Enterobacteriaceae - Muhammad Shoaib; Ashfaq Hussain; Luqman Satti; Wajid Hussain; Gohar Zaman; Faisal Hanif (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Using GIS tools to detect the land use/land cover changes during forty years in Lodhran District of Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Waseem Akram; Hafiz Mohkum Hammad; Mazhar Ali; Nasir Masood; Asad Amin; Hafiz Umar Farid; Syeda Refat Sultana; Shah Fahad; Depeng Wang; et al. (Environmental Science and Pollution Research, 2020)

Halotolerant potassium solubilizing plant growth promoting rhizobacteria may improve potassium availability under saline conditions - Muhammad Ashfaq; Hasnuri Mat Hassan; Amir Hamzah Ahmad Ghazali; Maqshoof Ahmad (Environmental Monitoring and Assessment, 2020)

Climate change impacts and adaptations for wheat employing multiple climate and crop modelsin Pakistan - Jamshad Hussain; Tasneem Khaliq; Senthold Asseng; Umer Saeed; Ashfaq Ahmad; Burhan Ahmad; Ishfaq Ahmad; Muhammad Fahad; Muhammad Awais; Asmat Ullah; Gerrit Hoogenboom (Climatic Change, 2020)

Modeling regional precipitation over the Indus River basin of Pakistan using statistical downscaling - Muhammad Saleem Pomee; Moetasim Ashfaq; Bashir Ahmad; Elke Hertig (Theoretical and Applied Climatology, 2020)
Complex processes govern spatiotemporal distribution of precipitation within the high-mountainous headwater regions (commonly known as the upper Indus basin (UIB)), of the Indus River basin of Pakistan. Reliable precipitation simulations particularly over the UIB present a major scientific challenge due to regional complexity and inadequate observational coverage. Here, we present a statistical downscaling approach to model observed precipitation of the entire Indus basin, with a focus on UIB within available data constraints. Taking advantage of recent high altitude (HA) observatories, we perform precipitation regionalization using K-means cluster analysis to demonstrate effectiveness of low-altitude stations to provide useful precipitation inferences over more uncertain and hydrologically important HA of the UIB. We further employ generalized linear models (GLM) with gamma and Tweedie distributions to identify major dynamic and thermodynamic drivers from a reanalysis dataset within a robust cross-validation framework that explain observed spatiotemporal precipitation patterns across the Indus basin. Final statistical models demonstrate higher predictability to resolve precipitation variability over wetter southern Himalayans and different lower Indus regions, by mainly using different dynamic predictors. The modeling framework also shows an adequate performance over more complex and uncertain trans-Himalayans and the northwestern regions of the UIB, particularly during the seasons dominated by the westerly circulations. However, the cryosphere-dominated trans-Himalayan regions, which largely govern the basin hydrology, require relatively complex models that contain dynamic and thermodynamic circulations. We also analyzed relevant atmospheric circulations during precipitation anomalies over the UIB, to evaluate physical consistency of the statistical models, as an additional measure of reliability. Overall, our results suggest that such circulation-based statistical downscaling has the potential to improve our understanding towards distinct features of the regional-scale precipitation across the upper and lower Indus basin. Such understanding should help to assess the response of this complex, data-scarce, and climate-sensitive river basin amid future climatic changes, to serve communal and scientific interests.

Bioaccumulation of lead in different varieties of wheat plant irrigated with wastewater in remote agricultural regions - Wuyi Liu; Asma Zafar; Zafar Iqbal Khan; Muhammad Nadeem; Kafeel Ahmad; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq (Environmental Science and Pollution Research, 2020)

Assessing the climate change impacts and adaptation strategies for rice production in Punjab, Pakistan - Ghulam Shabbir; Tasneem Khaliq; Ashfaq Ahmad; Muhammad Saqib (Environmental Science and Pollution Research, 2020)

Linking environment, malaria, and agricultural returns: a labor time use analysis at different stages of production using 3SLS - Sobia Rose; Muhammad Faisal Ali; Khuda Bakhsh; Muhammad Ashfaq; Sarfraz Hassan (Environmental Science and Pollution Research, 2020)

First report of cucurbit aphid borne yellows virus (CABYV) infecting melon in Pakistan - Muhammad Ahsan; Muhammad Ashfaq; Tariq Mukhtar; Nadeem Akhtar Abbasi; Zohaib Asad (Journal of Plant Pathology, 2020)

A study on the seasonal transfer of two metals from pasture to animals: health risk assessment - Zafar Iqbal Khan; Mubeen Akhtar; Kafeel Ahmad; Asma Ashfaq; Muhammad Nadeem; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik (Environmental Science and Pollution Research, 2020)

Use of crop growth model to simulate the impact of climate change on yield of various wheat cultivars under different agro-environmental conditions in Khyber Pakhtunkhwa, Pakistan - Farhana Gul; Ishfaq Ahmed; Muhammad Ashfaq; Dawood Jan; Shah Fahad; Xiuling Li; Depeng Wang; Muhammad Fahad; Muhammad Fayyaz; Syed Attaullah Shah (Arabian Journal of Geosciences, 2020)

Study of land cover/land use changes using RS and GIS: a case study of Multan district, Pakistan - Sajjad Hussain; Muhammad Mubeen; Waseem Akram; Ashfaq Ahmad; Muhammad Habib-ur-Rahman; Abdul Ghaffar; Asad Amin; Muhammad Awais; Hafiz Umar Farid; Amjad Farooq; Wajid Nasim (Environmental Monitoring and Assessment, 2020)

Comparison of water use efficiency, profitability and consumer preferences of different rice varieties in Punjab, Pakistan - Muhammad Asad ur Rehman Naseer; Muhammad Ashfaq; Amar Razzaq; Qamar Ali (Paddy and Water Environment, 2020)

Socio-political and ecological stresses on traditional pastoral systems: A review - Khurshid Muhammad; Nafees Mohammad; Khan Abdullah; Somuncu Mehmet; Ahmad Khan Ashfaq; Rashid Wajid (Journal of Geographical Sciences, 2019)

Feedstock-induced changes in composition and stability of biochar derived from different agricultural wastes - Tayyba Kanwal Choudhary; Khalid Saifullah Khan; Qaiser Hussain; Munir Ahmad; Muhammad Ashfaq (Arabian Journal of Geosciences, 2019)

Evaluation of toxic potential of metals in wheat crop grown in wastewater-contaminated soil in Punjab, Pakistan - Zafar Iqbal Khan; Kafeel Ahmad; Fauzia Batool; Kinza Wajid; Naunain Mehmood; Asma Ashfaq; Humayun Bashir; Muhammad Nadeem; Saif Ullah (Environmental Science and Pollution Research, 2019)

Residues of endosulfan in cotton growing area of Vehari, Pakistan: an assessment of knowledge and awareness of pesticide use and health risks - Ashfaq Ahmad; Muhammad Shahid; Sana Khalid; Habiba Zaffar; Tatheer Naqvi; Arshid Pervez; Muhammad Bilal; Muhammad Arif Ali; Ghulam Abbas; Wajid Nasim (Environmental Science and Pollution Research, 2019)

Toxicological potential of cobalt in forage for ruminants grown in polluted soil: a health risk assessment from trace metal pollution for livestock - Zafar Iqbal Khan; Nimra Arshad; Kafeel Ahmad; Muhammad Nadeem; Asma Ashfaq; Kinza Wajid; Humayun Bashir; Mudasra Munir; Bushra Huma; Hafsa Memoona; Madiha Sana; Khalid Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Assessing the socio-economic impact of climate change on wheat production in Khyber Pakhtunkhwa, Pakistan - Farhana Gul; Dawood Jan; Muhammad Ashfaq (Environmental Science and Pollution Research, 2019)

Optimizing irrigation and nitrogen requirements for maize through empirical modeling in semi-arid environment - Ishfaq Ahmad; Syed Aftab Wajid; Ashfaq Ahmad; Muhammad Jehanzeb Masud Cheema; Jasmeet Judge (Environmental Science and Pollution Research, 2019)

Chemical investigations of Si-rich organic and inorganic amendments and correlation analysis between different chemical composition and Si contents in amendments - Muhammad Irfan Sohail; Muhammad Zia ur Rehman; Ghulam Murtaza; Muhammad Ashfaq Wahid (Arabian Journal of Geosciences, 2019)

Deadly outbreak of chickenpox at district Faisalabad, Pakistan: possible causes, and preventive way forward - Muhammad Zubair Yousaf; Sadia Zia; Khalid Mahmood Anjum; Usman Ali Ashfaq; Muhammad Imran; Samia Afzal; Muhammad Sarfaraz Iqbal (Molecular Biology Reports, 2018)

Susceptibility of Asian citrus psyllid, Diaphorina citri (Hemiptera: Liviidae), to the insecticide afidopyropen: a new and potent modulator of insect transient receptor potential channels - Xue Dong Chen; Muhammad Ashfaq; Lukasz L. Stelinski (Applied Entomology and Zoology, 2018)

Yield Forecasting of Spring Maize Using Remote Sensing and Crop Modeling in Faisalabad-Punjab Pakistan - Ishfaq Ahmad; Umer Saeed; Muhammad Fahad; Asmat Ullah; M. Habib ur Rahman; Ashfaq Ahmad; Jasmeet Judge (Journal of the Indian Society of Remote Sensing, 2018)

First report of a cucumber mosaic virus (CMV) subgroup II isolate infecting pea in Pakistan - Muhammad Ahsan; Muhammad Ashfaq (Journal of Plant Pathology, 2018)

Epigallocatechin Gallate as an anti-obesity therapeutic compound: an in silico approach for structure-based drug designing - Muhammad Shahid Javaid; Noreen Latief; Bushra Ijaz; Usman Ali Ashfaq (Natural Product Research, 2018)

Flood hazards: household vulnerability and resilience in disaster-prone districts of Khyber Pakhtunkhwa province, Pakistan - Ashfaq Ahmad Shah; Jingzhong Ye; Muhammad Abid; Jahangir Khan; Syed Muhammad Amir (Natural Hazards, 2018)

Genetic diversity and recombination analysis based on capsid protein gene of Chilli veinal mottle virus isolates from Pakistan - Adnan Ahmad; Muhammad Ashfaq (European Journal of Plant Pathology, 2018)

Potential Toxic Metal Accumulation in Soil, Forage and Blood Plasma of Buffaloes Sampled from Jhang, Pakistan - Zafar Iqbal Khan; Ilker Ugulu; Sara Umar; Kafeel Ahmad; Naunain Mehmood; Asma Ashfaq; Humayun Bashir; Muhammad Sohail (Bulletin of Environmental Contamination and Toxicology, 2018)

Correction to: Pre-existing Small Vessel Disease in Patients with Acute Stroke from the Middle East, Southeast Asia, and Philippines - Naveed Akhtar; Abdul Salam; Saadat Kamran; Atlantic D’Souza; Yahia Imam; Pablo Garcia Bermejo; Muhammad Faisal Wadiwala; Ahmed Own; Ahmed ElSotouhy; Surjith Vattoth; Paula Bourke; Zain Bhutta; et al. (Translational Stroke Research, 2018)

Metal accumulation in Raphanus sativus and Brassica rapa: an assessment of potential health risk for inhabitants in Punjab, Pakistan - Kafeel Ahmad; Asma Ashfaq; Zafar Iqbal Khan; Humayun Bashir; Muhammad Sohail; Naunain Mehmood; Yunus Dogan (Environmental Science and Pollution Research, 2018)

Medicinal plant phytochemicals and their inhibitory activities against pancreatic lipase: molecular docking combined with molecular dynamics simulation approach - Bilal Ahmed; Usman Ali Ashfaq; Muhammad Usman Mirza (Natural Product Research, 2018)

Potential impacts of climate change and adaptation strategies for sunflower in Pakistan - Muhammad Awais; Aftab Wajid; Muhammad Farrukh Saleem; Wajid Nasim; Ashfaq Ahmad; Muhammad Aown Sammar Raza; Muhammad Usman Bashir; Muhammad Mubeen; Hafiz Mohkum Hammad; Muhammad Habib ur Rahman; Umer Saeed; Muhammad Naveed Arshad; et al. (Environmental Science and Pollution Research, 2018)

Barcode index numbers expedite quarantine inspections and aid the interception of nonindigenous mealybugs (Pseudococcidae) - Jing-Mei Ren; Muhammad Ashfaq; Xu-Nan Hu; Jun Ma; Fan Liang; Paul D. N. Hebert; Li Lin; Jean François Germain; Muhammad Z. Ahmed (Biological Invasions, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Radiation efficiency and nitrogen fertilizer impacts on sunflower crop in contrasting environments of Punjab, Pakistan - Wajid Nasim; Ashfaq Ahmad; Asad Amin; Muhammad Tariq; Muhammad Awais; Muhammad Saqib; Khawar Jabran; Ghulam Mustafa Shah; Syeda Refat Sultana; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Muhammad Zaffar Hashmi; et al. (Environmental Science and Pollution Research, 2018)

Determinants of flood risk mitigation strategies at household level: a case of Khyber Pakhtunkhwa (KP) province, Pakistan - Ashfaq Ahmad Shah; Jingzhong Ye; Muhammad Abid; Raza Ullah (Natural Hazards, 2017)

Disaster risk management in agriculture: tragedies of the smallholders - Raza Ullah; Ganesh P. Shivakoti; Farhad Zulfiqar; Muhammad Nadeem Iqbal; Ashfaq Ahmad Shah (Natural Hazards, 2017)

Nitrogen and plant population change radiation capture and utilization capacity of sunflower in semi-arid environment - Muhammad Awais; Aftab Wajid; Muhammad Usman Bashir; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Ashfaq Ahmad; Muhammad Farrukh Saleem; Hafiz Mohkum Hammad; Muhammad Mubeen; Umer Saeed; Muhammad Naveed Arshad; Shah Fahad; et al. (Environmental Science and Pollution Research, 2017)

Development of Eudragit RS 100 Microparticles Loaded with Ropinirole: Optimization and In Vitro Evaluation Studies - Prince Muhammad Kashif; Asadullah Madni; Muhammad Ashfaq; Mubashar Rehman; Muhammad Ahmad Mahmood; Muhammad Imran Khan; Nayab Tahir (AAPS PharmSciTech, 2017)

MPD3: a useful medicinal plants database for drug designing - Arooj Mumtaz; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Farooq Anwar; Faisal Gulzar; Muhammad Amjad Ali; Nazamid Saari; Muhammad Tariq Pervez (Natural Product Research, 2017)

A new irregular monoterpene acetate along with eight known compounds with antifungal potential from the aerial parts of Artemisia incisa Pamp (Asteraceae) - Mamoon Ur Rashid; Muhammad Alamzeb; Saqib Ali; Zafar Ali Shah; Ishrat Naz; Ashfaq Ahmad Khan; Dima Semaan; Mohammad Rafiullah Khan (Natural Product Research, 2017)

Antiviral phytochemicals identification from Azadirachta indica leaves against HCV NS3 protease: an in silico approach - Usman Ali Ashfaq; Asma Jalil; Muhammad Tahir ul Qamar (Natural Product Research, 2016)

AM1 is a potential ABA substitute for drought tolerance as revealed by physiological and ultra-structural responses of oilseed rape - Muhammad Shahbaz Naeem; Lulu Dai; Farooq Ahmad; Ashfaq Ahmad; Jun Li; Chunlei Zhang (Acta Physiologiae Plantarum, 2016)

Inoculation of Nicotiana tabacum with recombinant potato virus X induces RNA interference in the solenopsis mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Arif Muhammad Khan; Muhammad Ashfaq; Azhar Abbas Khan; Akhtar Rasool; Javed Iqbal; Shahid Mansoor (Biotechnology Letters, 2015)

Isolation, structure elucidation and enzyme inhibition studies of a new hydroxy ester and other compounds from Berberis jaeschkeana Schneid stem - Muhammad Alamzeb; M. Rafiullah Khan; Mamoon-Ur-Rashid; Saqib Ali; Ashfaq Ahmad Khan (Natural Product Research, 2015)

A new isoquinoline alkaloid with anti-microbial properties from Berberis jaeschkeana Schneid. var. jaeschkeana - Muhammad Alamzeb; M. Rafiullah Khan; Saqib Ali; Ashfaq Ahmad Khan (Natural Product Research, 2015)

Synthesis, molecular docking and antiviral screening of novel N′-substitutedbenzylidene-2-(4-methyl-5,5-dioxido-3-phenylbenzo[e]pyrazolo[4,3-c][1,2]thiazin-1(4H)-yl)acetohydrazides - Sana Aslam; Matloob Ahmad; Muhammad Makshoof Athar; Usman Ali Ashfaq; John M. Gardiner; Catherine Montero; Mervi Detorio; Masood Parvez; Raymond F. Schinazi (Medicinal Chemistry Research, 2014)

Maize seedling phosphorus nutrition: Allocation of remobilized seed phosphorus reserves and external phosphorus uptake to seedling roots and shoots during early growth stages - Muhammad Nadeem; Alain Mollier; Christian Morel; Muhammad Shahid; Muhammad Aslam; Muhammad Zia-ur-Rehman; Muhammad Ashfaq Wahid; Sylvain Pellerin (Plant and Soil, 2013)

Application of the CSM-CERES-Rice model for evaluation of plant density and irrigation management of transplanted rice for an irrigated semiarid environment - Shakeel Ahmad; Ashfaq Ahmad; Hakoomat Ali; Abid Hussain; Axel Garcia y Garcia; Muhammad Azam Khan; Muhammad Zia-Ul-Haq; Mirza Hasanuzzaman; Gerrit Hoogenboom (Irrigation Science, 2013)

Residual efficacy of thiamethoxam, Beauveria bassiana (Balsamo) Vuillemin, and diatomaceous earth formulation against Rhyzopertha dominica F. (Coleoptera: Bostrychidae) - Waqas Wakil; Tahira Riasat; Muhammad Ashfaq (Journal of Pest Science, 2012)

Application of the CSM-CERES-Rice model for evaluation of plant density and nitrogen management of fine transplanted rice for an irrigated semiarid environment - Shakeel Ahmad; Ashfaq Ahmad; Cecilia Manuela Tojo Soler; Hakoomat Ali; Muhammad Zia-Ul-Haq; Jakarat Anothai; Abid Hussain; Gerrit Hoogenboom; Mirza Hasanuzzaman (Precision Agriculture, 2012)

Synthesis, characterization, and urease inhibition of 5-substituted-8-methyl-2H-pyrido[1,2-a]pyrimidine-2,4(3H)-diones - Abdul Rauf; Sumaira Liaqat; Ashfaq M. Qureshi; Muhammad Yaqub; Aziz U. Rehman; Mahmood U. Hassan; Zahid H. Chohan; Faiz U. H. Nasim; T. Ben Hadda (Medicinal Chemistry Research, 2012)

Effect of Beauveria bassiana mixed with diatomaceous earth on mortality, mycosis and sporulation of Rhyzopertha dominica on stored wheat - Tahira Riasat; Waqas Wakil; Muhammad Ashfaq; Shahbaz Talib Sahi (Phytoparasitica, 2011)

Integrated management of Helicoverpa armigera in chickpea in rainfed areas of Punjab, Pakistan - Waqas Wakil; Muhammad Ashfaq; M. U. Ghazanfar; Muhammad Afzal; Tahira Riasat (Phytoparasitica, 2009)

Longifoside-A and -B: Two new cerebrosides from Mentha longifolia (Lamiaceae) - Muhammad Shaiq Ali; Waqar Ahmed; Muhammad Saleem; Mohammad Ashfaq Ali (Natural Product Research, 2006)